2015
DOI: 10.1111/ajad.12276
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of psychological distress in linking childhood maltreatment and alcohol use in young adulthood

Abstract: Background and Objectives Childhood maltreatment is related to alcohol use as well as psychological distress in young adulthood. Few studies have examined whether psychological distress mediates the relationship between child maltreatment and alcohol use. We examined the role of psychological distress in linking child maltreatment subtypes (ie, emotional abuse, physical abuse, sexual abuse, neglect) to four patterns of alcohol use, including frequency of alcohol use, binge drinking, alcohol-related problems, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
(74 reference statements)
0
25
1
Order By: Relevance
“…In treatment‐seeking alcohol‐dependent subjects, childhood trauma, emotional abuse in particular, was found to influence severity of alcohol dependency, and the effect was mediated by neuroticism . In a large pooled sample, the effect of childhood (sexual or physical) abuse and exposure to violent crime on substance dependency was mediated via mood and anxiety disorders, while in a population study, significant mediated effects were found between emotional abuse and alcohol‐related problems via psychological distress . In the present population study, the effects of all five CAT domains on alcohol problems were mainly mediated via depressive symptoms.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In treatment‐seeking alcohol‐dependent subjects, childhood trauma, emotional abuse in particular, was found to influence severity of alcohol dependency, and the effect was mediated by neuroticism . In a large pooled sample, the effect of childhood (sexual or physical) abuse and exposure to violent crime on substance dependency was mediated via mood and anxiety disorders, while in a population study, significant mediated effects were found between emotional abuse and alcohol‐related problems via psychological distress . In the present population study, the effects of all five CAT domains on alcohol problems were mainly mediated via depressive symptoms.…”
Section: Discussioncontrasting
confidence: 45%
“…In today's CAT literature, emotional (EmoAb) and physical abuse (PhyAB), emotional (EmoNeg) and physical neglect (PhyNeg), and sexual abuse (SexAb) are generally regarded as core CAT domains . However, few studies related to alcohol dependence and only one population study of APs have considered all five CAT domains, and even fewer gender differences concurrently. However, CAT and their effects on suicidal thoughts and behaviour, for example, may vary by gender, and be mediated via mental problems, depression in particular; thus, analyzing gender differences and associations in females and males separately are justified as suggested by Miller et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple traumas gave no further explanation to the variance of age of onset in the multiple regression analyses. Childhood emotional abuse may be related to psychological distress, which in turn, can be further associated with pathological drinking outcomes such as AD [38], although this was not investigated further in this study. Consistent with previous research, we also found that childhood sexual abuse was associated with an earlier age of onset of AUD [14,22].…”
Section: Discussionmentioning
confidence: 95%
“…although AUD and smoking usually co-occur, studies showed that smoker adolescents have a higher vulnerability to AUDs 7,8 . Other factors include internet addiction 9,10 , social anxiety 11 , child abuse 12-suggested that among the four forms of childhood maltreatment, emotional abuse could be the main driver of pathological drinking among victims of child abuse 14 .…”
mentioning
confidence: 99%